Analysis Of Traditional Games Understanding During Post Pandemi Covid-19 Lectures In 2020 Student Study Program Sports Sciences FIKK-UNESA - Aji Nurudin Araniri; Sudijandoko, Andun (Journal of Physical and Outdoor Education, 2023)
This study aims to determine the understanding of traditional games during lectures after the Covid-19 pandemic in class 2020 students of the FIKK-UNESA sports science study program. This study uses a qualitative descriptive research type with percentages. The sample in this study were students of the 2020 FIKK-UNESA sports science study program, totaling 35 students using a sampling technique, namely purposive sampling. Based on the results of the data concluded using the SWOT analysis that FIKK-UNESA class 2020 students' understanding of traditional Indonesian sports has a strength of 65%, weakness of 6%, opportunity of 4%, and threats by 3%. So it can be concluded that as many as 35 sports science students class of 2020 FIKK-UNESA have a good category understanding of traditional games by 65%.